2011
DOI: 10.3109/14017431.2011.563318
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment after treatment with pectoral muscle flaps because of deep sternal wound infection

Abstract: Objective. Pectoral muscle flaps (PMF) are effective in terminating protracted sternal wound infections (SWI) but long-term outcome remains uncertain. Therefore, the aim of this study was to evaluate long-term outcome in patients treated with PMF. Design. Thirty-four of 263 patients revised because of deep SWI from 1991-2005 were treated with PMF. Of the 21 patients alive, 11 had left-sided, two right-sided and eight bilateral procedures. Sternal debridement without closure of the sternum was done in 17 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…They found significant longterm disability in one third of patients. Sternum had not been closed in half the patients after debridement and the fact that the function of right arm and shoulder was affected more often despite the majority of procedures being left sided suggests that loss of skeletal continuity of the chest wall was more disabling than loss of pectoral muscle function [ 36 ]. Longstanding sternal non-union of 5 to 48 months was treated by pectoralis major muscle flap reconstruction in 24 patients over a 15 years period by Cabbabe and colleagues who reported dramatic improvement in symptoms of pain, popping and grinding [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…They found significant longterm disability in one third of patients. Sternum had not been closed in half the patients after debridement and the fact that the function of right arm and shoulder was affected more often despite the majority of procedures being left sided suggests that loss of skeletal continuity of the chest wall was more disabling than loss of pectoral muscle function [ 36 ]. Longstanding sternal non-union of 5 to 48 months was treated by pectoralis major muscle flap reconstruction in 24 patients over a 15 years period by Cabbabe and colleagues who reported dramatic improvement in symptoms of pain, popping and grinding [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…A study published in 2011 reported the long‐term complications in 19 patients after using the bilateral pectoralis major muscle flap for sternotomy closure. After a mean follow up of almost 6 years, more than half of these patients reported an unstable chest, two‐thirds of them reported difficulty in daily activities, and 37% reported problems with dressing· In that same study, 32% of patients preferred an alternative treatment at the time of flap harvesting, to avoid chest instability, even if such treatment could delay the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The flaps used in sternal reconstruction include pectoralis major muscle flap, rectus abdominis muscle or musculocutaneous flap, omentum, latissimus dorsi muscle or musculocutaneous flap, as well as their combination [15], and more recently a deep superior epigastric perforator (DSEP) flap [16]. Many of these options do not cover the entire length of the sternal defect or are associated with donor site morbidity and multiple potential complications including functional disability, hernias, seromas and pain [1,3,8,10,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The operation is brief and the muscles are easy to dissect. However, dividing the muscle's humeral insertion may lead to a functional defect[17,20,31]. The advancement flaps may not reach sufficiently to cover the defects in the most caudal third of the sternum.…”
mentioning
confidence: 99%